EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
In Malaysia, at a time when the Ministry of Education has called for greater roles amongst teachers to improve teaching for their students and for teacher educators to educate teachers for a rapidly changing world, it is important that this journal acts as means to increase our understanding for effective organisation, pedagogy, assessment, and use of technology in schools and in teacher education. Journal of Research, Policy & Practice of Teachers and Teacher Education (JRPPTTE) has always encouraged authors to contribute articles that can help develop both theoretical and practical understanding of the processes and implications of what teachers and teacher educators do. Topics that have been published over JRPPTTE over the last few issues are typically broad and represent diverse orientations towards teachers, teaching and teacher education as well as differing methodologies for studying them. The six articles in this issue continue to follow that pattern and represents varied genres, topics and methodologies.